From ambition to action: Unlocking climate finance for locally led resilience in Africa - Tesfaye, Lidya; Jalango, Dorcas; Chilambe, Pedro; Nzuki, Esther (2025)
This side event, co-organized by the Alliance of Bioversity International and CIAT and the Global Green Growth Institute (GGGI), brought together policymakers, financial institutions, researchers, civil society leaders, and communication experts to advance dialogue on scaling locally led climate action and strengthening climate-resilient food systems in Africa. Building on the momentum of the Africa Climate Summit (ACS2), the discussion underscored the importance of aligning national climate ambitions with community priorities to ensure adaptation efforts are responsive, inclusive, and effective. Participants explored practical models, structured tools and participatory planning can unlock finance and accelerate implementation at local levels. The event also highlighted the role of innovative financing mechanisms, risk-sharing instruments, and effective communication strategies in de-risking investments, expanding community engagement, and strengthening ownership. The session helped chart actionable pathways to translate climate ambition into grounded and equitable adaptation outcomes ahead of COP30.